Stock Prices Reaction to Oil Price Fluctuations: Empirical Evidence from Nigeria - Inegbedion, Henry; Obadiaru, Eseosa; Adeyemi, Olamide (International Journal of Energy Economics and Policy, 2020)
The study investigated stock market reactions to oil price fluctuations in Nigeria. A longitudinal design consisting of data on the Nigerian Stock market index, crude oil prices, exchange rate, interest rate, inflation rate and GDP for the period 1984-2019 was employed. The data were subjected to stationarity and cointegration tests using ADF and Johansen’s techniques. Based on the results of the stationarity and cointegration tests, Vector error correction model was used to analyse the research data. The results indicate that crude oil prices have short-run and long-run effects on stock market returns. Exchange rate was found to have significant short-run effect on stock market returns. Keywords: Stock market returns; crude oil prices; oil price fluctuations; exchange rate; interest rate JEL Classification: H25 DOI: https://doi.org/10.32479/ijeep.8306